Teratoma of larynx: case report - Srivastava, Rakesh; Tandon, Vini (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Teratomas are embryonal neoplasm arises from totipotent germ cells. They are having tissues from all the three blastodermic layers. There are various locations of congenital teratoma. Naso-oropharyngeal site teratoma are either sessile or pedunculated. We describe a rare case of laryngeal teratoma in a five years old patient presented with change in voice and breathing difficulty. On flexible laryngoscopy, it appeared like supraglottic cyst but on CT scan it was confirmed as teratoma. Pre-operative tracheostomy and transoral carbon dioxide laser assisted excision done. Histopathological examination showed osteoid trabeculae, chondroid tissue with loose myxoid islands and adipose tissue. No recurrence of tumor on 18 months follow-up. This is the first case report of pediatric larynx teratoma reported in present century.